Pengembangan Buku Saku Interaktif sebagai Media Pembelajaran Etika Profesi pada Mahasiswa Pendidikan Tata Boga - Karl Frizts Pasaribu; Vina Gabriella Saragih; Refli Renaldi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The teaching of Professional Ethics in the Culinary Arts Study Program is often delivered in a theoretical manner, make lack of contextual and reflective learning experiences for students. This study aims to develop and evaluate an interactive pocket book as a learning medium to support students' understanding of ethical values in real culinary work settings. The research employed the 4-D development model (Define, Design, Develop, Disseminate), with data collected through observation, interviews, expert validation, practicality questionnaires, and pretest–posttest design. The study was conducted over three months at Universitas Negeri Medan. Validation results indicated that the media was highly feasible in terms of content, layout, and language. Practicality testing showed that students found the media very practical, while the effectiveness test revealed an improvement in learning outcomes with a gain score of 0.60 (moderate to high category). These findings demonstrate that the interactive pocket book is effective in promoting ethical learning that is contextual, reflective, and applicable. The media is recommended for integration into learning strategies focused on values and professional attitudes and is suggested for further development into digital formats to enhance flexibility and wider accessibility.